International academic franchises: Identifying the benefits of international academic franchise provision. (31st March 2014) - Pon, Kevin; Ritchie, Caroline
This paper is an exploratory study of the benefits that institutions of higher education can gain when entering into partnerships of academic franchising, an international activity which has been increasing in popularity over the past few decades. The paper looks at the current literature on academic franchising and then goes on to study, through case studies and direct observation, franchising from the perspective of four different institutions in four different countries. The paper reveals that very often there are multiple benefits to be gained which are not necessarily sought when the institutions enter such partnerships. Contrary to previous academic literature the study also reveals that there is a much greater flow of these benefits from one institution to another and thus provides a new richer model that has changed from the 'parent child' model to that of a more evenly balanced model where both partners are benefiting from mutual cooperation.